THE INSPECTION OF LABORIOUS MECHANICAL ASPECTS FOR EFL READERS - Moriyanti Moriyanti; Nyak Mutia Ismail (Getsempena English Education Journal, 2022)
As most students admitted that their problem in reading was mainly regarding vocabulary, the authors were drawn to a premise that there must be a stronger underpinning explanation leading to such comprehension gap in reading. This study aimed at finding out a specific root-problem faced by EFL learners when performing reading, which are the mechanic skills of reading. This study was conducted using qualitative approach—case study design. The respondents were 55 college students in Aceh, Indonesia who were sophomores in Economics and Business faculty. The data were collected from September-December 2019. The data source was a weekly individual checklist based on the mechanical reading framework, namely: phonic-phonemic awareness-vocabulary-fluency-comprehension to find out which problem they repeatedly faced during the reading process. From 14 meetings, it was calculated that 54 students mostly faced fluency problem which means that they know the semantic and literal meaning of a certain word but struggle with the sense of the word. Later, the problem faced was comprehension which was faced by 20 students. Then, the problem of vocabulary was experienced by 16 students. And the least problem faced is phonemic problem which was faced by 1 student only.